La fertilización y su incidencia en el crecimiento de plántulas de Cordia alliodora (Ruiz & Pavón) Oken en el vivero de la finca experimental La Represa, Cantón Quevedo, Provincia de Los Ríos. - Guerrero Quintana, Alex Adonis (2020)
Fertilization has played a fundamental role in forestry development since the beginning of time, when forestry engineers looked for a way to make their crops more technical and exhaustively monitor their development, which is why this research work seeks to determine the incidence of the fertilization in the growth of Cordia alliodora (Ruiz & Pavón) Oken seedlings, through the analysis of the dasometric measurements of the application of 3 differe nt dosages in time intervals. During this investigation it was observed that the dosages used managed to obtain an average germination percentage of 95% and an average mortality rate of 3.5%, that is, that the fertilizers did not show harm to the seedlings. On the other hand, the data collection in the field work was carried out in the UTEQ nursery, where all the spaces and tools were made availab le to carry out this project. The methodology used for the development of this research was analytical and quantitative, since it is based on the study of measurements obtained in an experimental design; The results showed that the dose applied in treatment number two with the dosage of 10 cc, Kelpack, 5 cc Yara Vita, 5 cc EverGreen, for each liter of water, was the one that brought the highest performance in relation to height and diameter in development. seedlings of Cordia alliodora (Ruiz & Pavón) Oken, showing a linear and superior growth in each of the measurements carried out, especially in comparison with the plants that were not exposed to any type of fertilizer. This research work proposes, in synthesis, that looking for the most effective and effic ie nt dosage results in many benefits for the producer, since it translates into a better use of the final shift and the wood obtained; No unnecessary production costs and environmental damage. Key words: Fertilizers, height, diameter, number of leaves and doses.